Effects of initial oxide on microstructural and mechanical properties of friction stir welded AA2219 alloy. (5th December 2015) - Chen, H.B.; Wang, J.F.; Zhen, G.D.; Chen, S.B.; Lin, T.
Abstract: Effects of various initial surface oxide films on microstructural and mechanical properties of friction stir welded (FSW) joints have been studied in the present paper. Anodizing was adopted to produce oxidation on AA2219-T62 surface. A series of friction stir welded joints were produced with various initial surface oxidations to study the effects on microstructural and mechanical properties of the joints. X-ray radiography inspection was conducted to determine the existence of welding defects. Optical microscopy (OM), scanning electron microscope (SEM) and transmission electron microscope (TEM) were used to characterize stir zone features and microstructure. Tensile test was employed to obtain FSW joint mechanical properties. Results show that initial surface oxide film has pronounced effect on the joint line remnant (JLR) distribution, microcosmic appearance and mechanical properties. Further analysis of the JLR particles suggests that the dispersed particles are Al2 O3 oxide with the characteristics of polycrystalline structure because of the effect of the thermo-mechanical cycles. In addition, tensile strength of FSW joints with JLR inside the stir zone only reached about 60% of a sound FSW joint. Fractography analysis of broken tensile specimens exposed a series of severe "scalloping" correlated with JLR flaw, while sound weld exhibits fine dimples on the fracture surface. Graphical abstract: Highlights: Amorphous Al2 O3 film becomes polycrystalline through friction stir welding (FSW). Retaining oxide film prior to FSW is the main cause to form joint line remnant defect. Existence of joint line remnant defect reduces FSW joint strength dramatically.